Craniosynostosis: literature review - Tirado Pérez, Irina Suley; Sequeda Monterroza, José Fernando; Zarate Vergara, Andrea Carolina (Universidad y Salud, 2016)
The craniosynostosis consist of full or partial premature closure of one or more cranial sutures, with an incidence of 1 in 1000 3000 live births, with higher prevalence in males. Within the context of primary craniosynostosis, sagittal craniosynostosis scaphocephaly or is the most common and known form. To occur over a period of life where growth cranium is very important causes in children a characteristic skull deformity should be corrected, since otherwise and being progressive, aesthetic involvement can be very undesirable; functional alterations that may occur include increased intracranial pressure, seizures and others. A search was conducted in databases such as PUBMED, RIMA, MEDLINE, Medscape reviews issues, management guides, articles and statistical analysis, in english, where they found 1,469 references. After a first look at the articles through their summaries included in the period 2000 to 2014, finally 50 articles were selected in full text covering the subject fully meeting the conditions search.